SEKOLAH DASAR LUAR BIASA B BANJARBARU - Luthfiah Fitri Anisa; Rudi Hartono (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The design of the Special Needs Elementary School B Banjarbaru is based on Law of the Republic of Indonesia Number 20 of 2003 Article 5 Paragraph 1, which guarantees the right of every citizen, including children with special needs (ABK) who are deaf, to receive quality education. The urgency of this design arises because hearing impairment is the second most common disability in Banjarbaru City. However, a specialized school focusing solely on hearing impairment with adequate facilities is not yet available. SDLB B Banjarbaru focuses on deaf students, therefore, the concept is the deafspace with its five principles: sensory reach, space and proximity, mobility and proximity, light and color, and acoustics. Thus, it is hoped that this concept can address the problem, which is the fulfillment of the SDLB B Banjarbaru design with adequate facilities and infrastructure for deaf children.